New record of the genus Amblypalpus Mitrofanov & Strunkova (Acari, Prostigmata, Tenuipalpidae) with description of a new species from Saudi Arabia - Nasreldeen Ahmed Elgoni; Jawwad Hassan Mirza; Fahad Jaber Alatawi (Biodiversity Data Journal, 2025)
Amblypalpus Mitrofanov & Strunkova (Prostigmata, Tenuipalpidae) is a small genus in the family Tenuipalpidae, representing five species reported from Iran, Tajikistan and South Africa. This study describes a new species of Amblypalpus, A. pisoniae sp. nov., reported from the south-western region (Jazan) of Saudi Arabia (SA).The genus Amblypalpus Mitrofanov & Strunkova is reported for the first time from SA, collected from Pisonia sp. (Nyctaginaceae) with a new species, A. pisoniae sp. nov. The new species is described and illustrated, based on females and males. Additionally, the diagnosis of the genus Amblypalpus is updated.